Acceptance tests conducted on optical ground wires for checking additional fibre length - Marthen, W; Thomas, R (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
Optical fibres integrated into overhead phase and earth conductors have been more and more used as communication links in the context of high voltage transmission line networks. In designing and manufacturing these conductors it is essential to take account of the fact that the glass fibre is highly sensitive to axial and lateral strain as well as bending. The quality of the system-meaning optical fibre and surrounding conductor structure-can only be assessed by carrying out tests which simulate real-life loads. This means taking into account not only those parts of the stranded conductor that are in direct contact with the glass fibre-such as the gel, for example-but the entire system, including also the connections and fixing means. The authors describe the acceptance and creep tests for these cables. (2 pages)